Hacking habitat art of control : art, technology and social change - Gevers, Ine 1960-; Bresser, Nina (Niet Normaal Foundation, 2016)
Hacking Habitat presents a pressing, topical theme that appeals to a wide audience: the way we are controlled by technological systems and the way counterforces are organized. Innovation goes hand in hand with control: surveillance cameras observe us and inimitable Google algorithms manipulate our behaviour. We risk losing control over our lives. Worldwide, people are waking up to the fact that they need to regain control of their lives and reclaim their living environment (habitat). This lavishly illustrated book presents the work of over 80 international artists working at the intersection of art, technology and social change, including Susan Hiller, William Kentridge, Aram Bartholl, Joseph Beuys, Melanie Bonajo, Metahaven, Johan Grimonprez, Laura Kurgan and Roy Villevoye. In a collection of exploratory and persuasive essays, Hacking Habitat makes us aware of the high-tech systems that have control over our society, and provides tools to use to escape the regulation and control.